Circulating fluidized bed combustion ash as controlled low-strength material (CLSM) by alkaline activation. (15th December 2017) - Park, S.M.; Lee, N.K.; Lee, H.K.
Highlights: CLSM was fabricated using alkaline activation of CFBC ashes. CLSM satisfied the properties outlined in ACI 229. Ettringite was identified as a main reaction product. Abstract: The present study is aimed at providing a useful means of treating and utilizing the CFBC ash as controlled low-strength material (CLSM). The CLSM in this study was produced by activating a mixture of CFBC fly ash, bottom ash and blast furnace slag with sodium hydroxide (NaOH) solution. The characteristics of the CLSM were evaluated by the main factors such as flow, bleeding and compressive strength as stated in ACI 229, along with initial setting time and XRD patterns. The CLSM showed delayed strength development due to the reactivity of calcium sulfate in CFBC fly ash and bottom ash. This effect is evidenced by the XRD pattern of the CLSM at 7 and 56 d which showed the consumption of gypsum as a source of calcium sulfate, to produce the reaction product ettringite.